2011
DOI: 10.1016/j.ajhg.2011.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Studying Gene and Gene-Environment Effects of Uncommon and Common Variants on Continuous Traits: A Marker-Set Approach Using Gene-Trait Similarity Regression

Abstract: Genomic association analyses of complex traits demand statistical tools that are capable of detecting small effects of common and rare variants and modeling complex interaction effects and yet are computationally feasible. In this work, we introduce a similarity-based regression method for assessing the main genetic and interaction effects of a group of markers on quantitative traits. The method uses genetic similarity to aggregate information from multiple polymorphic sites and integrates adaptive weights tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
134
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(135 citation statements)
references
References 55 publications
1
134
0
Order By: Relevance
“…For the joint test (Figure 2, bottom), the relative power of SimReg vs. min-P is similar to what was observed for the G3E tests. Furthermore, the relative performance between SimReg and min-P for binary traits is similar to what was observed for quantitative traits (Tzeng et al 2011). …”
supporting
confidence: 59%
See 4 more Smart Citations
“…For the joint test (Figure 2, bottom), the relative power of SimReg vs. min-P is similar to what was observed for the G3E tests. Furthermore, the relative performance between SimReg and min-P for binary traits is similar to what was observed for quantitative traits (Tzeng et al 2011). …”
supporting
confidence: 59%
“…Recently, Lin et al (2013) proposed a generalized linear mixedeffect model (GLMM) for G3E interactions for binary and continuous traits and showed it has superior power and robustness over min-P methods. A similar method, similarity regression (SimReg), proposed by Tzeng et al (2011) to study marker-set G3E for continuous traits, was shown to be connected to linear mixed-effect models.In this article, we extend the SimReg G3E framework established in Tzeng et al (2011) to binary traits with common or rare variants. SimReg, which is inspired by HasemanElston regression for linkage analysis (Haseman and Elston 1972;Elston et al 2000) and haplotype similarity tests for regional association (Tzeng et al 2003;Beckmann et al 2005), uses a regression model to correlate trait similarity with genetic similarity across multiple loci and to account for covariates.…”
mentioning
confidence: 99%
See 3 more Smart Citations